With the mine in the veins: emotional adjustments in female partners of Chilean mining workers. Issue 12 (1st December 2016) - Silva-Segovia, Jimena; Salinas-Meruane, Paulina
Abstract: This research analyzes emotional adjustments and imbalances experienced by female partners of Chilean mining workers, resulting from interacting demands of work, intimacy, family, and handling money, as well as tensions caused by miners' prolonged absences and dissimilar schedules, negatively impacting family encounters. The research is circumscribed in northern Chile, in the Region of Antofagasta, epicenter of worldwide copper mining. Through a qualitative design, 36 in-depth interviews were held and a sociodemographic survey of mining workers' partners. Among the findings are power conflicts derived from the role that workers and female partners have as a couple, in managing money and in emotional aspects, exacerbated by gender constructions of 'the paid miner' and 'female partner'. Female partners express their challenges in managing the family's economic resources as well as emotional aspects between the partners.